AKTIVITAS LARVISIDAL EKSTRAK ETIL ASETAT DAN HEKSANA DARI FILTRAT Beauveria bassiana TERHADAP Aedes aegypti - I Nyoman Pugeg Aryantha; Wahyu Setyaji Dwiantara (BERITA BIOLOGI, 2019)
Beauveria bassiana produces several metabolites that are toxic to insects so that it can be used as a biological insect control agent as an alternative to synthetic pesticides. The aim of this study was to determine the larvicidal activity of ethyl acetate and hexane extract from B. bassiana filtrate culture against Aedes aegypti 2nd instar larvae. This research was it cooked by determining the optimum age of spore inoculum of B. bassiana on the Potato Dextrose Agar (PDA) based on the number of spores and its viability. Afterwards, we determine the incubation time of B. bassiana in the Potato Dextrose Broth (PDB) in order to obtain filtrate culture which have highest mortality effects against Ae. aegypti 2nd instar larvae. B. bassiana filtrate culture was extracted with hexane and ethyl acetate and tested aegypti for larvicidal activity with a concentration range of 50, 100, 200, 300 ppm. The LC50 value was carried out by probit analysis. The results showed that ninth day old culture in the PDA was the optimum age of spore inoculum with the spore number and viability were 2.54 x 107 spore/mL and 93.46% respectively. The filtrate of sixth day old culture in PDB medium gave 100% mortality against 2nd instar Ae. Aegypti larvae. LC50 values of ethyl acetate and hexane extract were 117.28 dan 287.09 ppm. These results showed that the ethyl acetate and hexane extract of B. bassiana filtrate culture have biopesticide potential against 2nd instar Ae. aegypti larvae.